PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN MENGGUNAKAN MODEL TPS BERBANTUAN MEDIA KONKRET PADA SISWA KELAS V SDN 075/VII KASANG MELINTANG - Kalimah; Puput Wahyu Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low mathematics learning outcomes of fifth grade students at SDN 075/VII Kasang Melintang, especially on fraction material. The purpose of this study was to improve student learning outcomes on fraction material by applying the Think Pair Share (TPS) cooperative learning model assisted by concrete media. This research used Classroom Action Research (CAR) method with Kemmis and McTaggart design consisting of two cycles. Each cycle includes planning, action, observation, and reflection stages. The subjects of this research were 24 students of class V SDN 075/VII Kasang Melintang. Data collection techniques used observation, tests, and documentation. The results showed that in the pre-cycle stage the average student learning outcomes were 54.17 with a classical completeness of 29.17%. In cycle I the average increased to 67.08 with classical completeness of 58.33%. In cycle II the average increased significantly to 80.42 with classical completeness reaching 87.50%, which has exceeded the determined success indicator of 80%. It can be concluded that the application of the TPS model assisted by concrete media can significantly improve the mathematics learning outcomes of fifth grade students at SDN 075/VII Kasang Melintang on fraction material.